A Case for Handy and Puku‘i’s Ethnographic Reconstruction of the Polynesian Family System in Hawai‘i - Dye, Thomas S (Waka Kuaka, 2021)
A case for Handy and Puku‘i’s early-twentieth-century ethnographic reconstruction of the Polynesian family system in the Hawaiian Islands is made in the light of a theory of cognatic descent groups associated with land. They describe land tenure practices as organised by commoners who worked in named land parcels known as ‘ili ‘āina. This description is rejected by many scholars today, who argue that Handy and Puku‘i interpreted Hawaiian land tenure as organised by egocentric kindreds, rather than corporate groups. These scholars argue that commoners lost the ability to organise land tenure prior to European contact in 1778. Here I propose that this argument rests on an ahistorical reading of Handy and Puku‘i, which was exposed by Goodenough’s 1955 landmark paper, “A Problem in Malayo-Polynesian Social Organization”. I identify two types of corporate groups associated with land in traditional Hawaiian society, including the social category of maka‘āinana and its constituent ‘ili ‘āina. Together, maka‘āinana and ‘ili ‘āina constituted an efficient land tenure system capable of allocating labour to produce a reliable surplus. The event that ended commoner organisation of land tenure in Hawai‘i was the mid-nineteenth-century Great Māhele—the process of land redistribution proposed by the King Kamehameha III.